Illustrated handbook of food hygiene & quality management. (3G E-Learning, 2018)
"This book illustrates pitfalls in food safety management and provides key insight into the means of avoiding them. An essential text for students dealing with food science, public health, microbiology, environmental health and the food service industry"--Provided by publisher.